2015
DOI: 10.1142/s0192415x15500044
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Effect of Electroacupuncture on Paclitaxel-Induced Neuropathic Pain via Spinal Opioidergic and Adrenergic Mechanisms in Mice

Abstract: This study was designed to determine the antinociceptive effect and related neuronal mechanism of electroacupuncture (EA) on paclitaxel (PTX)-induced neuropathic pain in mice. PTX (4 mg/kg, i.p.) was administered once a day for 5 consecutive days to induce neuropathic pain. EA stimulation (2 mA, 2 Hz, 30 min) was applied at the ST36 acupoint bilaterally once in every 2 days. Repeated EA stimulation significantly attenuated PTX-induced mechanical allodynia and thermal hyperalgesia. In a separate set of experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…This approach did not induce robotic inflammation or damage of the colon but produced visceral hypersensitivity at adult. Adrenergic signaling has been reported to participate in the inflammatory and neuropathic pain states 24 28 . Here we demonstrated that application of propranolol resulted in a significant analgesic effect in IBS rats.…”
Section: Discussionmentioning
confidence: 99%
“…This approach did not induce robotic inflammation or damage of the colon but produced visceral hypersensitivity at adult. Adrenergic signaling has been reported to participate in the inflammatory and neuropathic pain states 24 28 . Here we demonstrated that application of propranolol resulted in a significant analgesic effect in IBS rats.…”
Section: Discussionmentioning
confidence: 99%
“…To assess nociceptive responses to innocuous mechanical stimuli (mechanical allodynia), we measured paw withdrawal response frequency (PWF) by using von Frey filament (2.0 g, North Coast Medical, Morgan Hill, CA, USA) as describe previously38. A von Frey filament was applied from underneath the metal mesh flooring to each plantar of hind paw.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this test can differentiate antinociceptive effect of drug from adverse side effect such as sedation. As following the method described previously38, mice were placed on a cylindrical platform (12 cm wide; 3 cm diameter) suspended 33 cm above the bottom of the apparatus (SciTech Korea Inc., Seoul, Korea). Falls were cushioned by wood shaving bedding.…”
Section: Methodsmentioning
confidence: 99%
“…Basic research demonstrated that EA significantly inhibited mechanical allodynia/ hyperalgesia in rodents with PTX-evoked peripheral neuropathy. 5,6 In addition, combined treatment with EA and gabapentin (an analgesic drug) showed robust and enduring analgesic actions against PTX-induced neuropathy. 7 Furthermore, a phase IIA trial showed that acupuncture attenuated the severity of peripheral neuropathy induced by PTX chemotherapy in breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%